Peran Pemimpin Agama Berbasis Wawasan Pluralisme Dalam Merawat Toleransi Beragama di Indonesia - Ondrasi Gea; Hanna Dewi Aritonang; Senida Harefa (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:This article departs from reality regarding the existence of cases of conflict to acts of violence with religious motives in Indonesia. Intolerant attitudes are increasingly felt by adherents of certain religions, for example refusing to build houses of worship even though the requirements have been fulfilled, feelings of being disturbed by the worship activities of adherents of other religions, the emergence of narrowly fanatical statements about the celebration of certain religious holidays, the occurrence of hate speech and even religious blasphemy. It turned out that amid these cases of conflict and intolerant religious leaders were also involved. Therefore, the author aims to develop an idea about the role of religious leaders plays a role in maintaining inter-religious harmony in Indonesia, namely by strengthening tolerance based on pluralism insights. This research refers to various literature consist of books, articles, journals and observes events around religious harmony. To build tolerance with a pluralism perspective, religious leaders can organize seminars on pluralism, Pancasila, and ideas that maintain national harmonious and integrity. In addition, adequate religious education for religious leaders can influence attitudes toward the reality of a pluralistic society, especially religious plurality. The deeper the pluralism insight of religious leaders and their adherents, the better the rating of tolerance in Indonesia. Abstrak:Artikel ini bertolak dari sebuah realita mengenai adanya kasus-kasus konflik hingga tindakan kekerasan dengan motif agama di Indonesia. Sikap intoleran semakin dirasakan oleh penganut agama tertentu, misalnya penolakan pendirian rumah ibadah meskipun persyaratan sudah terpenuhi, perasaan terganggu dengan aktifitas ibadah pemeluk agama lain, timbulnya pernyataan bermuatan fanatik sempit terhadap perayaan hari besar agama tertentu, terjadinya ujaran kebencian bahkan penistaan agama. Ternyata di tengah kasus konflik dan intoleran tersebut, pemuka agama juga turut terlibat. Oleh karena itu, penulis bertujuan untuk mengembangkan sebuah ide tentang peran pemimpin agama merawat kerukunan antar umat beragama di Indonesia, yaitu dengan memperkuat toleransi berbasis wawasan pluralisme. Penelitian ini mengacu pada berbagai sumber literatur antara lain buku, artikel, jurnal dan mengamati peristiwa di sekitar kerukunan beragama. Untuk membangun toleransi berwawasan pluralisme, maka pemuka agama dapat membuat seminar bertajuk pluralisme, pancasila dan gagasan yang menjaga kerukunan serta keutuhan bangsa. Selain itu pendidikan agama yang memadai bagi pemuka agama dapat mempengaruhi sikap terhadap realitas masyarakat majemuk, terutama pluralitas agama. Sehingga semakin dalam wawasan pluralisme pemimpin agama beserta penganutnya, maka semakin baik tingkat toleransi di Indonesia.